Thyroid control of contractile function and calcium handling in neonatal rat heart - Kolár, F; Seppet, E K; Vetter, R; Procházka, J; Grünermel, J; Zilmer, K; Ostádal, B (Pflugers Archiv, 1992)
Newborn rats were rendered hyperthyroid (daily subcutaneous injections of L-triiodothyronine, 10 micrograms 100 g-1 body weight) or hypothyroid (0.05% 6-n-propyl-2-thiouracil in drinking water to nursing mothers) during the first 3 weeks of postnatal life. Compared with the euthyroid group, hyperthyroidism resulted in: (1) cardiac enlargement with right ventricular preponderance, (2) increased cardiac contractile function, (3) increased Ca2+ uptake by the sarcoplasmic reticulum (SR), (4) decreased sensitivity to the negative inotropic effect of verapamil and (5) greater inhibition of contractile function by ryanodine. Hypothyroidism generally resulted in opposite changes. The data suggest that the development of the heart and its contractile function during early postnatal life depends on the plasma level of thyroid hormones. In particular, the relative contribution of the SR and sarcolemmal Ca2+ transport to the control of cardiac contractility seems to be markedly affected by altered thyroid states. The postnatal maturation of the SR function is accelerated in hyperthyroidism but retarded in hypothyroidism. Consequently, hyperthyroid hearts appear to be less dependent and hypothyroid ones more dependent on trans-sarcolemmal Ca2+ fluxes when compared with age-matched euthyroid animals.
Keywords: Thyroid Gland; štítná žláza; Animals, Newborn; Calcium; Male; Rats, Inbred Strains; Thyroid Hormones; hormony štítné žlázy; vápník; Myocardium; mužské pohlaví; inbrední kmeny potkanů; novorozená zvířata; Body Weight; krysa rodu Rattus; Myocardial Contraction; Verapamil; Animals; Sarcoplasmic Reticulum; zvířata; Rats; kontrakce myokardu; myokard; ryanodin; Ryanodine; tělesná hmotnost; sarkoplazmatické retikulum; verapamil